Interests versus culture in the theory of institutional change? - Joachim Zweynert (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2007)
This paper suggests an analytical framework to bring two explanations of institutional change together. My analysis rests on three building blocks: Firstly on the idea of the transfer or transplantation of institutions, secondly on the idea of functional differentiation, and thirdly and decisively on an understanding of culture as a toolkit leaving room for interest, choice and strategic action. The concepts of institutional transplantation and of functional differentiation will be introduced in the following section. In the third one, I will reformulate North's neoclassical theory of the state and his elaborations on culture and belief systems in terms of these concepts. Section four, then, offers a proposal of how to bridge the gap between the two approaches. Throughout the paper, I will use the example of Russia to illustrate my theoretical thoughts, a country I have been studying for years and which, as North (1999,9) remarks, is particularly suited to explain the problems of economic change. In section five I will outline in very basic terms how the history of failed attempts at reforms in Russia might be interpreted from the perspective developed here.
Keywords: 330